Improving Amounting Ability Through Media Power Points in Grade II of Basic School - Siti Marwah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The problem that arises in this classroom action research is the low ability of students in learning addition. The purpose of this study was to develop learning steps using power point media to improve student learning outcomes. This classroom action research was the subject of second grade students of SDN Pedeslohor 02 semester I of the 2020/2021 school year. With 12 students, this classroom action research was conducted in 2 cycles, each cycle consisting of 4 stages, namely planning, implementing, observing and reflecting. The method of collecting research data is through tests and observations. The data analysis used quantitative descriptions. The results showed that through the power point media it could improve students' ability in addition. The average value of student learning outcomes in the pre-cycle was 60.9 and in the first cycle it reached 73.5 while the second cycle became 81. It can be concluded that through power point media it can improve students' learning ability.